Musical Characteristics and Playing Technique of Liszt’s Second Narrative - Song, Jinzhu (Journal of Social Science and Humanities, 2025)
Liszt was born in Hungary and is a representative composer of the age of romanticism. His creative style is innovative and personalized, and his outstanding compositions throughout his life are countless. The value of “Ballade No.2 in B minor” is one of Liszt’s relatively underestimated compositions. Firstly, this article analyzes the musical structure of the composition. Secondly, an analysis is conducted on the themes that occupy a significant amount of space, as well as the thematic transformation of each theme, in terms of musical image and. Finally, a more detailed explanation of the five most important musical features of the composition, namely “Symphonizing”, “Nationalism”, “Narrative”, “Dramatization”, and “Virtuosity”, is provided. The explanation of these five musical features is the frontier demonstration of this article. The author hopes to further explore the musical value of this piece by analyzing its musical features and interpretation methods, thereby providing references for future piano players.